Regional Specialisation and Geographic Concentration of the High-Tech Sector in European Union Countries - Małgorzata JUCHNIEWICZ; Magdalena ŁADA (Communications of International Proceedings, 2021)
Continuous economic development and the growing importance of advanced technologies employed by enterprises boost the significance of the high-tech sector in national economies, including those in the European Union. These changes are reflected in the products and services offered by the sector. High-tech enterprises are quick to adapt to the new conditions and requirements set by society. Since the sector has existed for a relatively short time and, due to its specific nature, it requires continuously expanding knowledge and research in many aspects – from its definition through the determination of its concentration in specific regions to an evaluation of its competitiveness and an impact on the changes in the regional and international economy. These considerations started with the classification of the high-tech sector and defining its regional specialisation and geographic concentration. Subsequently, selected indices, i.e. location index, specialisation index and a cluster index were used to identify the factors that determine the sector importance in European Union countries.
Keywords: High-Tech Sector; Regional Specialisation; Geographic Concentration; European Union.